Determinantes sociales de la salud mental: políticas públicas desde el modelo biopsicosocial en países latinoamericanos - Varinia Leiva- Peña; Patricia Rubí-González; Benjamin Vicente-Parada (Pan American Health Organization, 2021)
This article presents evidence on the implementation of public policies on mental health, and describes the advances and challenges to implementing the biopsychosocial and community model, mainly in Latin America. A theoretical review was conducted of articles indexed in Web of Science, Scopus, PubMed and SciELO. Government reports and programs were included. Social determinants impact mental health. In particular, poverty significantly increases the risk of developing a mental disorder. Accordingly, the World Health Organization insists on the need to adopt a biopsychosocial paradigm to address mental health challenges. About a third of countries still do not have a national mental health policy and there are large disparities in funding and population coverage between high- and low-income countries. Particularly in Latin America, the results illustrate progress in low- and middle-income countries in terms of developing mental health programs with a community and biopsychosocial approach. However, there are challenges in their operationalization, financing, and adaptation to socio-cultural realities. The evidence indicates that in order to move from a biomedical paradigm to one that incorporates the social determinants of health, identical strategies should not be employed in all communities, since the needs of low- and middle-income countries differ from those of high-income countries. Therefore, it is essential to increase local research to generate evidence that reflects national needs with regard to public policies on mental health.